Pesona Tari sebagai Aset Pariwisata Budaya Indonesia - Puspitaning Wulan; Warih Handayaningrum (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractDance has the complexity of the expression of aesthetic expressions that are correlated with other fields around it. This provides the opportunity for dance to be able to have an internal and external impact on individuals in and around the scope of dance. Therefore this study aims to explain (1) the charm in dance, (2) the need for self-expression that gives aesthetic experience, and (3) the long-term role of dance for tourism and cultural preservation. This study uses qualitative methods of dance and its potential in tourism. Alfred Gell's charm approach is used in which dancers process motion to attract the attention of the audience and give an aesthetic impact on the audience so as to bring up experiences that have implications for the field of tourism. The results showed that (1) the charm displayed in dance, whether through dancers' gestures, costumes, delivery or presentation, and ritual performances can provide cultural therapeutic elements, where these elements provide an aesthetic experience to the audience; (2) the need for aesthetic experience is ultimately able to provide tourist attraction for the audience so as to provide encouragement to enjoy dance performances as tourists; and (3) the government pays particular attention to dance as an agent and cultural tourism asset in Indonesia. The role of dance which is increasingly complex and routine opens opportunities for collaborative work with other disciplines to provide hope for the varied use of dance in Indonesia.Keyword: Enchantment, Dance, Cultural Tourism, Indonesia Abstrak Seni tari memiliki kompleksitas dari perujudan ekspresi estetis yang berkonstelasi dengan bidang lain disekitarnya. Hal tersebut memberikan peluang seni tari mampu memberikan dampak internal maupun eksternal individu dalam dan sekitar lingkup tari. Oleh karenanya penelitian ini bertujuan untuk menjelaskan tentang (1) pesona dalam seni tari, (2) kebutuhan akan ekspresi diri yang memberikan pengalaman estetik, dan (3) peran jangka panjang seni tari bagi pariwisata dan pelestarian budaya. Penelitian ini menggunakan metode kualitatif terhadap seni tari dan potensinya dalam pariwisata. Pendekatan pesona milik Alfred Gell digunakan di mana penari mengolah gerak guna menarik perhatian penonton dan memberikan dampak estetis pada penonton sehingga memunculkan pengalaman yang berimplikasi pada bidang pariwisata. Hasil penelitian menunjukkan bahwa (1) pesona yang ditampilkan dalam tari, baik melalui gerak tubuh penari, kostum, penyampaian atau penyajian, dan ritual pertunjukannya mampu memberikan unsur terapetik budaya, di mana unsur tersebut memberikan pengalaman estetik kepada penonton; (2) kebutuhan akan pengalaman estetik tersebut pada akhirnya mampu memberikan daya tarik wisata bagi penonton sehingga memberikan dorongan untuk menikmati pertunjukan tari sebagai wisatawan; dan (3) pemerintah memerhatikan seni tari secara khusus sebagai agen serta aset pariwisata budaya yang ada di Indonesia. Peran seni tari yang semakin kompleks dan rutin membuka peluang untuk terjadinya kerja kolaboratif dengan disiplin ilmu lain memberikan harapan akan variatifnya pemanfaatan seni tari di Indonesia.Kata kunci: Pesona; Seni Tari; Pariwisata Budaya; Indonesia